Konseling Individu Perilaku Terlambat melalui Pendekatan Behavioral Teknik Self Management - Adi Cahyo Gumelar (Jurnal Pendidikan Dasar dan Menengah (Dikdasmen), 2025)
The aim of this research is to find out how individual counseling with a behavioral approach to self-management techniques is applied to late behavior, at UPT SMKN 7 Makassar. The research method used in this research is qualitative research with a case study design. Data collection in this research can be obtained through direct observation and interviews. The research subjects were students with the initials K from class X AP 1 who had a history of often coming to school late. Efforts to handle late behavior are individual counseling using a behavioral approach, self-management techniques, with the aim of changing inappropriate behavior by strengthening expected behavior and eliminating unwanted behavior and helping to find appropriate behavior. After the evaluation was carried out, subject K experienced changes based on statements from the guidance and counseling teacher, homeroom teacher and subject teacher who stated that K had shown significant improvement compared to before. Thus, it can be concluded that the behavioral approach with self-management techniques is effective in dealing with clients' late behavior.